Optimalisasi Penggunaan Platform Canva untuk Fondasi Digital Kreatif di SMPN 11 Ngabang, Desa Amboyo Selatan - Syariq Jadzil Siregar; Mela Jelita; Renita Agustin; Dava Azril Ramadhani; Monika Natalia (CV. Ulil Albab Corp, 2026)
In today's digital era, mastering graphic design technology is an essential skill in the field of education. However, the use of design platforms such as Canva in junior high schools remains underutilized. This community service activity aims to enhance students' digital literacy and creativity through Canva training at SMPN 11 Ngabang, Desa Amboyo Selatan. The method used was a descriptive qualitative approach involving interviews, observations, and documentation conducted from July 7 to 24, 2025. The results show that 196 students from grades 7 to 9 successfully understood and used Canva to create designs such as logos, presentations, and posters. Several student works were applied in school activities, including class profile logos and extracurricular team branding. The training was met with enthusiastic responses from teachers, who viewed Canva as a useful educational tool and an innovative medium for developing students’ branding skills. This activity demonstrates that Canva training can serve as a foundation for sustainable creative digital literacy in the school environment.